Fifty years of wheat breeding in Southern Brazil: yield improvement and associated changes - Rodrigues, Osmar; Lhamby, Julio César Barreneche; Didonet, Agostinho Dirceu; Marchese, José Abramo (Pesquisa Agropecuaria Brasileira, 2007)
The objective of this study was to assess the impact of genetic breeding on grain yield, and to identify the physiological traits associated to the increment in yield and their related growth processes, for wheat cultivars grown in Southern Brazil, in the past five decades. Seven wheat cultivars released between 1940 and 1992, were compared for physiological aspects associated with grain yield. Grain yield, biological yield, biomass partitioning, harvest index and grain yield components were also determined. The number of grains per square meter was more affected by plant breeding and was better correlated with grain yield (r = 0.94, p
Keywords: Triticum aestivum; genetic gain; harvest index; yield components